Pengaruh Brand Image, Brand Awareness dan Brand Trust Terhadap Brand Loyalty Pengguna Smartphone Merek Samsung (Studi Kasus Pada Mahasiswa Fakultas Ekonomi dan Bisnis Unisma) (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
Abstract In this study to determine and analyze how much influence brand image, brand awareness and brand trust have on brand loyalty. What is done to Samsung brand smartphone users. Sampling was carried out on Students of the Faculty of Economics and Business, Islamic University of Malang, as many as 96 respondents. This study uses questionnaires in conducting research.The analytical method used is multiple linear analysis to determine the x variable against y. In this study it can be seen that brand image has a positive effect on bran loyalty, brand awareness has a positive effect on brand loyalty and brand trust has a positive effect on brand loyalty. And also brand image, brand awareness and brand trust have a positive effect simultaneously on brand loyalty. Keywords : Brand Image, brand awareness, brand trust, brand loyalt.